Understanding the Cross-Talk of Redox Metabolism and Fe-S Cluster Biogenesis in Leishmania Through Systems Biology Approach - Kumar, Anurag; Chauhan, Nutan; Singh, Shailza (Frontiers in Cellular and Infection Microbiology, 2019)
Leishmania parasites possess an exceptional oxidant and chemical defense mechanism, involving a very unique small molecular weight thiol, trypanothione (T[SH]2), that helps the parasite to manage its survival inside the host macrophage. The reduced state of T[SH]2 is maintained by NADPH-dependent trypanothione reductase (TryR) by recycling trypanothione disulfide (TS2). Along with its most important role as central reductant, T[SH]2 have also been assumed to regulate the activation of iron-sulfur cluster proteins (Fe/S). Fe/S clusters are versatile cofactors of various proteins and execute a much broader range of essential biological processes viz., TCA cycle, redox homeostasis, etc. Although, several Fe/S cluster proteins and their roles have been identified in Leishmania, some of the components of how T[SH]2 is involved in the regulation of Fe/S proteins remains to be explored. In pursuit of this aim, a systems biology approach was undertaken to get an insight into the overall picture to unravel how T[SH]2 synthesis and reduction is linked with the regulation of Fe/S cluster proteins and controls the redox homeostasis at a larger scale. In the current study, we constructed an in silico kinetic model of T[SH]2 metabolism. T[SH]2 reduction reaction was introduced with a perturbation in the form of its inhibition to predict the overall behavior of the model. The main control of reaction fluxes were exerted by TryR reaction rate that affected almost all the important reactions in the model. It was observed that the model was more sensitive to the perturbation introduced in TryR reaction, 5 to 6-fold. Furthermore, due to inhibition, the T[SH]2 synthesis rate was observed to be gradually decreased by 8 to 14-fold. This has also caused an elevated level of free radicals which apparently affected the activation of Fe/S cluster proteins. The present kinetic model has demonstrated the importance of T[SH]2 in leishmanial cellular redox metabolism. Hence, we suggest that, by designing highly potent and specific inhibitors of TryR enzyme, inhibition of T[SH]2 reduction and overall inhibition of most of the downstream pathways including Fe/S protein activation reactions, can be accomplished.